Business continuity and BS25999 : a combined glossary - Calder, Alan (ITG pocket guides., 2008)
The first glossary to present the full range of terms relating to business continuity BS25999 is the formal standard for business continuity management. This invaluable pocket guide will help you to understand the language of business continuity. It contains definitions both of the key words in BS25999 and of the relevant terms found in the information security standard, ISO27001. Other definitions provided in the glossary have been taken from the earlier glossaries published by the Business Continuity Institute and the DRI (Institute for Continuity Management), from the IT service management standard, ISO20000, and from the IT Infrastructure Library (ITILv3). Created to facilitate the adoption of BS25999, the combined glossary sets out the most common business continuity terms and offers an authoritative explanation of what they mean. It will therefore enable business continuity to be discussed clearly and consistently throughout the English-speaking world. Benefits to business include: Improve communication and cooperation Business continuity management requires commitment at boardroom level, and involves many different people within a given organisation. The purpose of this glossary is to facilitate communication and thereby make it easier for IT managers, business continuity professionals and senior executives to cooperate Find a glossary that is comprehensive Just as business continuity affects many different functions within the organisation, so it also touches upon other standards besides BS25999. This glossary combines definitions of words from BS25999 with terms both from other information security standards and from the IT Infrastructure Library. As the first truly comprehensive glossary of business continuity terms, this pocket guide is the only book where you can find an explanation of all the relevant business continuity terms in one place Stay in the loop If your organisation is setting up a business continuity management plan, you have a choice. Either you get involved in the process, or the key decisions will be taken without your input. If you want to be kept in the loop on business continuity planning, this guide can help you to understand what people are talking about and how it relates to your area of responsibility Help your staff to plan for an emergency Business continuity planning is a vital imperative for those public sector organisations that are responsible for frontline services. Under the UK Civil Contingencies Act...